1984
DOI: 10.1002/art.1780270507
|View full text |Cite
|
Sign up to set email alerts
|

Costs and outcomes in rheumatoid arthritis and osteoarthritis

Abstract: A prospective descriptive study was done on the direct and indirect costs to ambulatory patients with rheumatoid arthritis and osteoarthritis, stratified at study entry by level of function. Measures of health status over a 1-year period were taken. On a yearly basis, in 1979 dollars, patients spent an average of $147 for arthritis medications, aids, and devices, and $207 for outpatient visits. A small number were hospitalized and incurred an average charge of $245, and an additional $84 for physician fees. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(40 citation statements)
references
References 8 publications
0
39
0
1
Order By: Relevance
“…Studies relating function to costs are rare. However, in rheumatoid arthritis good functional status has been related to low medical treatment costs (Liang et al 1984.…”
Section: Discussionmentioning
confidence: 99%
“…Studies relating function to costs are rare. However, in rheumatoid arthritis good functional status has been related to low medical treatment costs (Liang et al 1984.…”
Section: Discussionmentioning
confidence: 99%
“…When medical therapy fails to control pain or physical functioning reaches an unacceptable level, total joint arthroplasty (TJA) of the hip or knee is indicated (3,4). Although TJA results in substantial reduction in pain and disability (3)(4)(5)(6)(7), studies indicate that candidates for surgery can be reluctant to consider TJA. For example, in a US study, many African Americans with advanced knee osteoarthritis (OA) reported being unwilling to have surgery, reflecting a belief that it would not significantly improve their current health (8).…”
Section: Introductionmentioning
confidence: 99%
“…2 3 Although the number of published reports on cost of illness in rheumatoid arthritis has increased considerably over the past decade, [4][5][6] most of the studies have applied a societal or a payer perspective and have not specifically addressed OOPE. Only few studies have examined OOPE in rheumatic conditions: Boonen et al 7 examined OOPE in 209 patients with ankylosing spondylitis and reported an average annual healthcare and non-healthcare expenditure of J431 per patient; Lapsely et al 8 reported particularly high OOPE for patients with advanced osteoarthritis, especially women in Australia; Lapsley et al 9 examined rheumatoid arthritis related OOPE in Australia and found an average annual spending of $A1513 (,J893; exchange rate as per July 2004: 1J = 0.59A$); in an early study by Liang et al, 10 the fraction covered by patient OOPE was estimated to account for at least 20% of total rheumatoid arthritis related direct costs; and finally, in a study by Cooper et al, 11 individuals with early inflammatory polyarthritis incurred a mean expenditure of £1297 over a six month period.…”
mentioning
confidence: 99%